7-Steps medication reviews: analysis of medicine changes in acute medical wards. (30th November 2022) - Brown, J; Hogg, A; Scullin, C; Fleming, G; Scott, M
Abstract: Introduction: In Northern Ireland, medication errors cause 20 patient deaths, lead to around 800 non-elective hospital admissions and cost £1.9 million annually. 1 The iSIMPATHY (implementing Stimulating Innovation in the Management of Polypharmacy and Adherence Through the Years) project is an EU-funded partnership between Scotland, Ireland and Northern Ireland delivering medication reviews using the 7-Steps medication review tool and asking 'what matters to you?'  2 The iSIMPATHY 7-Steps review is a new research study in Northern Ireland. Aim: To identify medicine changes made by an independent prescribing pharmacist during 7-Steps medication reviews. Method: Medication reviews were delivered on acute medical wards in the Northern Health and Social Care Trust. No patients were excluded from reviews, however reviews were targeted at patients aged 50 years and older and resident in a care home, approaching the end of their lives, prescribed 10 or more medicines or on high-risk medication. Data on medication changes made during 192 medication reviews was collected and analysed to identify the numbers and types of medicines stopped, started and doses altered. Ethical approval was not required, an approved Data Protection Impact Assessment was in place. Results: Mean number of medicines per patient pre- and post-review were 12.2 and 12.3 respectively. Medicines were stopped in 49% of patients, dose decreased in 36%, changed to a more appropriate medicine in 15%, dose increased in 15% and new medicines started in 55%. Medicines stopped included opioids and gabapentenoids (18%), nutritional and electrolyte supplements (15%), items for comfort (9%), antidepressants (including amitriptyline for pain) (10%), antihypertensives and diuretics (8%), bladder anticholinergics and mirabegron (5%), laxatives (4%), betahistine (3%), quinine (2%). Dose decreases were made for analgesics including opioids (28%), PPI/H2RA (23%), anticoagulants (13%), statins and fibrates (6%), antihypertensives (6%), benzodiazepines and z-drugs (5%), antidiabetics (3%). Dose increases were made for anticoagulants and items for comfort (both 26%), laxatives (24%), pancreatin (15%), nutritional and electrolyte supplements (9%). Medicines started included nutritional and electrolyte supplements (45%), medicines for comfort (19%), laxatives (15%), nicotine replacement (7%), PPI/H2RA (2%), bisphosphonates (2%). Discussion/Conclusion: The 7-STEPS medicine reviews led to important medicine changes while the number of medicines following review remained the same. The person-centred, holistic approach facilitated identification and actioning of the medicine changes that mattered to individual patients. Stopped and decreased dose medicines included high risk medicines, those likely to cause adverse effects or high anticholinergic burden and medicines no longer needed or effective for the individual. Medicine doses were increased for high risk medicines, to ensure sufficient nutritional, electrolyte and enzyme replacement and items for comfort for example constipation. Importantly, unmet therapeutic needs were identified and new medicines were prescribed to address these needs, for example, acid suppressants, bisphosphonates, anticoagulants, statins, antidiabetics, nicotine replacement therapy and for patient's comfort including pain relief. Limitations include results may not be reflective of all hospital patients as set in an acute setting and through the iSIMPATHY project. References: 1. Transforming medication safety in Northern Ireland, Department of Health 2022. Available from: https://www.health-ni.gov.uk/sites/default/files/publications/health/Transforming-medication-safety-in-Northern-Ireland_1.pdf 2. iSimpathy. Making Medication Personal. 2022. Available from: https://www.isimpathy.eu/